Construction workers’ behaviour: case study of Ghanaian construction industry - Mustapha, Zakari; Akomah, Benjamin Boahene; Tieru, Chris K. (UiTM Press, 2025)
Many construction industries suffer from the consequences of employee behaviour. Human factors increase efficiency and performance in the construction industry, leading to project success. The completion time of projects, within approved costs, and the required quality are important to employers. This study examined the factors that influence employee behaviour among construction professionals (quantity surveyors, structural engineers, and architects) at construction sites within the Cape Coast North Metropolis in the Central Region of Ghana. A survey was used to collect data from 120 construction professionals. Out of 120 questionnaires administered among construction employees,96 questionnaires were returned, and this represents 80% of the response rate. The findings show that motivation, incentive programs, recognition, leadership style, and safety measures affect employee behaviour at construction sites. The study concludes that employers should be motivated, and competent supervisors should be employed to manage the site. Safety measures should be prioritised for on-site employers. It is recommended that these factors be seriously considered to achieve productivity.